Pengembangan Karakter Melalui Materi Berbagai Pekerjaan - Syifa Dilla Khansa; Melani Khalimatu Sa’diyah; Tin Rustini (FKIP, Universitas Palangka Raya, 2024)
Through social studies learning which contains moral concepts, values, attitudes and skills for living everyday life, students are expected to be able to apply them to their daily lives. In social studies learning about various jobs, the expected achievement is the goal of how character development is achieved in the learning. Trained participants are invited to understand. This is the achievement hoped for in this paper. This qualitative research was conducted to determine the impact of character development through occupational diversity on elementary school students in learning social sciences (IPS), and with this, we as researchers know the impact and results of learning about occupational diversity to elementary school students. Achieving children's character with good behavior, good manners, morals and ethics, as well as how to blend into society.